Happy Mix Creative Gymnastics Development in Rhythmic Gymnastics Learning Elementary School Students (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The rhythmic gymnastics material given in learning does not have many choices and tends to be the same, causing children not to be optimal in learning. The purpose of this study was to produce a model for the development of Happy Mix creative gymnastics for elementary school students. The research method used is Research & Development which includes; needs analysis, observation and interviews, as well as literature review, initial product creation, design validation by gymnastics lecturers, fitness gymnastics experts and physical education learning experts, trial I, product revision by experts, trial II, final product revision, final model results Happy Mix creative exercise. Collecting data using a questionnaire. The data analysis technique used is descriptive percentage. The results of product development research in the form of Happy Mix gymnastics that can be used as an alternative to rhythmic gymnastics learning. Based on the results of the questionnaire and the observation of the first trial, data obtained on the average cognitive aspect of 83%, affective average of 87% and psychomotor on average 91%. The results of the questionnaire and observation of the second trial obtained data for the cognitive aspect on average 84%, affective average 92%, and psychomotor an average 88%. The conclusion of this study is that the Happy Mix creative exercise model can be applied to Physical education learning, especially in learning rhythmic gymnastics or rhythmic motion in elementary schools.